2011
DOI: 10.1111/j.1600-0536.2011.01921.x
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre patch testing with a resol resin based on phenol and formaldehyde

Abstract: The contact allergy frequency in the tested population (1.1%) merits its inclusion in the Swedish baseline series and possibly also in other baseline series. Simultaneous allergic reactions were noted to colophonium, M. pereirae, and fragrance mix I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
0
5
1
Order By: Relevance
“…The frequency of allergic reactions to PFR2 during the screening period at the FIOH was higher than that in the two previous multicentre screening studies . This is not surprising, as all of our patients are referred for suspected occupational contact allergy.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…The frequency of allergic reactions to PFR2 during the screening period at the FIOH was higher than that in the two previous multicentre screening studies . This is not surprising, as all of our patients are referred for suspected occupational contact allergy.…”
Section: Discussioncontrasting
confidence: 53%
“…Five centres in Sweden included PFR2 (Chemotechnique, Vellinge, Sweden) in their baseline series, and reported a high frequency (1.1%) of allergic reactions in the patch‐tested population. This study did not assess the clinical relevance of the allergic reactions . Simultaneous reactions were noted for colophonium, Myroxylon pereirae , and fragrance mix I.…”
mentioning
confidence: 93%
“…A study from Sweden, in which five centres included PFR2 in their baseline series between 2006 and 2007, found a rate of 1.1% of CA in the patch tested population, however clinical relevance was not assessed 13 . Similarly, the ICDRG reported a comparable frequency of positive reactions of 1.2% (28 patients) out of 2259 patients assessed to PFR2 as part of a baseline series, in 13 centres between September 2012 and February 2013 14 .…”
Section: Discussionmentioning
confidence: 99%
“…as a test substance is a good marker of contact allergy to various phenol formaldehyde resins (50,60). Allergic reactions to this test preparation are common: 1.1% of patch-tested patients in Sweden reacted positively [61] and in an international study the frequency was 1.2% [62]. In the latter study, clinical relevance was only found in 25% of the cases.…”
Section: Patch Testingmentioning
confidence: 90%